2014
DOI: 10.1890/13-1955.1
|View full text |Cite
|
Sign up to set email alerts
|

Empirical tests of within‐ and across‐species energetics in a diverse plant community

Abstract: 19Many fundamental properties of ecological systems and interactions are tied to body size, and a 20 related metric, the metabolic rate distribution, both within and across species. A previously 21proposed Maximum Entropy Theory of Ecology (METE) predicts numerous interrelated 22 macroecological patterns, including spatial distributions of individuals within species, abundance 23 distributions across species, species area relationships, and distributions of metabolic rates of all 24 individuals within a commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 33 publications
2
64
0
Order By: Relevance
“…Regardless of the underlying reason that the models performed similarly, our results indicate that the SAD usually does not contain sufficient information to distinguish among the possible statistical processes—let alone biological processes—with any degree of certainty (Volkov et al, 2005), though it is possible that this result differs in marine systems (see Connolly et al, 2014). A more promising way to draw inferences about ecological processes is to evaluate each model’s ability to simultaneously explain multiple macroecological patterns, rather than relying on a single pattern like the SAD (McGill, 2003; McGill, Maurer & Weiser, 2006; Newman et al, 2014; Xiao, McGlinn & White, 2015). It has also been suggested that examining second-order effects, such as the scale-dependence of macroecological patterns (Blonder et al, 2014) or how the parameters of the distribution change across gradients (Mac Nally et al, 2014), can provide better inference about process from these kinds of pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the underlying reason that the models performed similarly, our results indicate that the SAD usually does not contain sufficient information to distinguish among the possible statistical processes—let alone biological processes—with any degree of certainty (Volkov et al, 2005), though it is possible that this result differs in marine systems (see Connolly et al, 2014). A more promising way to draw inferences about ecological processes is to evaluate each model’s ability to simultaneously explain multiple macroecological patterns, rather than relying on a single pattern like the SAD (McGill, 2003; McGill, Maurer & Weiser, 2006; Newman et al, 2014; Xiao, McGlinn & White, 2015). It has also been suggested that examining second-order effects, such as the scale-dependence of macroecological patterns (Blonder et al, 2014) or how the parameters of the distribution change across gradients (Mac Nally et al, 2014), can provide better inference about process from these kinds of pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Because the deviation between the patterns predicted by theory and empirical data from disturbed systems appears to itself follow a systematic pattern (Newman et al . ; Rominger et al ., in prep. ), clues exist for how to extend the static theory to the dynamic realm.…”
Section: Background On the Maximum Entropy Theory Of Ecologymentioning
confidence: 98%
“…; Harte, Smith & Storch ; Harte ; White, Thibault & Xiao ; Newman et al . ); however, a great deal of further testing is needed to establish METE's generality, strengths and weaknesses. Existing tests have focused on SADs or SARs while tests of metabolic rate distributions are rare (but see Harte ; Newman et al .…”
Section: Background On the Maximum Entropy Theory Of Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly relevant given that METE does not universally succeed in predicting macroecological patterns (Newman et al . ; Xiao et al . ), potentially due to system‐specific biological constraints being ignored, and the issue was raised in earlier METE papers (Harte et al .…”
Section: Introductionmentioning
confidence: 99%